2016
DOI: 10.7554/elife.17159
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methylation facilitates KCNQ channel-PIP2 interaction leading to seizure suppression

Abstract: KCNQ channels are critical determinants of neuronal excitability, thus emerging as a novel target of anti-epileptic drugs. To date, the mechanisms of KCNQ channel modulation have been mostly characterized to be inhibitory via Gq-coupled receptors, Ca2+/CaM, and protein kinase C. Here we demonstrate that methylation of KCNQ by protein arginine methyltransferase 1 (Prmt1) positively regulates KCNQ channel activity, thereby preventing neuronal hyperexcitability. Prmt1+/- mice exhibit epileptic seizures. Methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…In vitro experiments identified 4 modified arginine residues, R333, R345, R353, and R435, on KCNQ2 that also reside in the PIP2-binding region. These modifications require PRMT1 but do not appear to need its close relative PRMT8 122 . PIP2 could not fully rescue M-currents in neurons of PRMT1 heterozygous mice; this points to the involvement or redundancy of other PRMTs.…”
Section: Inflammationmentioning
confidence: 91%
See 1 more Smart Citation
“…In vitro experiments identified 4 modified arginine residues, R333, R345, R353, and R435, on KCNQ2 that also reside in the PIP2-binding region. These modifications require PRMT1 but do not appear to need its close relative PRMT8 122 . PIP2 could not fully rescue M-currents in neurons of PRMT1 heterozygous mice; this points to the involvement or redundancy of other PRMTs.…”
Section: Inflammationmentioning
confidence: 91%
“…Dysregulation of the KCNQ genes is one underlying cause of epilepsy. In a mouse model, PRMT1 heterozygotes have impulsive seizures and their brains feature lower expression of asymmetrically dimethylated KCNQ2 relative to wild types 122 . Further, methylated KCNQ had higher affinity for their binding partner phosphatidylinositol-4,5-bisphosphate (PIP2).…”
Section: Inflammationmentioning
confidence: 99%
“…While phosphorylation of Kv7 subunits is typically associated with channel suppression, phosphorylation of Kv7-bound CaM by protein kinase CK2 has been shown to facilitate CaM interaction with the channel, increasing PIP 2 efficacy and increasing channel amplitude while remaining sensitive to increases in intracellular Ca 2+ [43,134]. Another signaling pathway known to augment the M-current (specifically, channels containing Kv7.2/4/5 subunits) is through the increase in an intracellular reactive oxygen species, ROS [135,136]. It has been shown that the oxidation of three cysteine residues lying within the S2–S3 linker increase the P o of Kv7 channels [135].…”
Section: Kv7 Channel Augmentationmentioning
confidence: 99%
“…It has been shown that the oxidation of three cysteine residues lying within the S2–S3 linker increase the P o of Kv7 channels [135]. Another recently identified pathway for ROS induced augmentation is methylation of arginine residues of Kv7.2 subunit by arginine methyltransferase 1 (Prmt1), which promotes Kv7.2 interaction with PIP 2 [136]. This study also suggests that partial methylation of arginine residues in Kv7 channels is essential for maintaining basal M-current [136].…”
Section: Kv7 Channel Augmentationmentioning
confidence: 99%
“…Recently we and others reported augmentation of KCNQ channel activity via the oxidative modification of a triple-cysteine pocket in the channel S2-S3 linker (11,24,32). Because zinc can bind to cysteines and form redox-sensitive molecular switches (33), we tested if the effect of zinc on KCNQ channels is also redox dependent and mediated by the triple-cysteine pocket.…”
Section: +mentioning
confidence: 99%